A culturally-specific education strategy to improve stroke health literacy in Vietnamese communities in South Western Sydney - Jessica Ly; Christopher Blair; Helen Badge; Michael Camit; Khoi Do; Timmy Pham; Nicola Chappelow; Dennis J. Cordato; Mark W. Parsons (Dialogues in Health)
Background: South-Western Sydney (SWS) is home to a large Vietnamese community, who are at higher risk of stroke and adverse health outcomes than Australian-born individuals. There is limited research on the effect of educational interventions on stroke literacy in Vietnamese communities. This study aimed to characterise recognition of stroke symptoms, risk/protective factors, and stroke response in Vietnamese communities living in SWS and investigate whether culturally tailored education sessions could improve stroke literacy. Methods: A prospective interventional study evaluated a single 1.5-h stroke education workshop. Data included pre/post-education surveys, participant demographics and stroke literacy. Change in literacy and contributing factors were analysed. Results: There were 195 participants in three sessions. Stroke symptoms were recognised by the majority [Face:(56.4 %), Arms:(66.7 %), Speech:(61.5 %)], with 52.8 % identifying all three whilst 29.2 % recognised none. Most participants were confident calling an ambulance (60.0 %), aware of diabetes as a risk factor (73.9 %) and recognised healthy diet/exercise (82.5 %) as protective factors. Post-education, 24.6 % recognised more symptoms, with 73.4 % identifying all three and only 16.6 % recognising none. 33.1 % were more confident calling an ambulance, 32.4 % more aware of diabetes mellitus, and 29.8 % more aware of diet/exercise. Smaller group size [OR = 2.83, 95 %CI = 1.15–6.96 (p = 0.024), lower age [OR = 0.93, 95 %CI = 0.87–1.00 (p = 0.037)] and lower baseline literacy [OR = 6.38, 95 %CI = 2.48–16.41 (p < 0.001)] were significantly associated with improved stroke literacy post-education. Conclusion: Stroke literacy in the SWS Vietnamese community improved with a single culturally tailored education session. This study underscores the importance of tailored educational interventions and highlights the need for strategies addressing low baseline literacy and age-related barriers.